Student funding: The case of disabled students in South African higher education: - Ndlovu, S.; Woldegiorgis, E. T. (South African Journal of Higher Education, 2023)
By virtue of many countries’ existence within neoliberal and capitalist systems, in which education is commodified, students with economic disadvantage find themselves in a precarious position in terms of funding, resulting in limited access to education in higher education. While many of disadvantaged students confront challenges of funding resulting in continuous indebtedness in higher education in South Africa, the situation is exacerbated for the disabled ones, who have extra economic needs when it comes to their education. The empirical study, informed by specific concepts from Decolonial Theory and Critical Disability Studies informed understanding of funding for disabled students at one university in South Africa. The finding was that while a specific funding model for disability was available, it was inadequate for learning of those with disabilities resulting in their continued indebtedness and exclusion from the system. The study sought to engage in the debate of inadequate funding in the Global South, which keeps students from economic disadvantage, including the disabled ones in debt, thereby disempowering them and making it difficult for them to contribute meaningfully to the decolonisation project in higher education largely, and making change.